2018
DOI: 10.15252/embj.201899506
|View full text |Cite
|
Sign up to set email alerts
|

Loss of VGLL 4 suppresses tumor PD ‐L1 expression and immune evasion

Abstract: Targeting immune checkpoints, such as PD‐L1 and its receptor PD‐1, has opened a new avenue for treating cancers. Understanding the regulatory mechanism of PD‐L1 and PD‐1 will improve the clinical response rate and efficacy of PD‐1/PD‐L1 blockade in cancer patients and the development of combinatorial strategies. VGLL4 inhibits YAP‐induced cell proliferation and tumorigenesis through competition with YAP for binding to TEADs. However, whether VGLL4 has a role in anti‐tumor immunity is largely unknown. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 57 publications
(103 reference statements)
3
49
0
Order By: Relevance
“…This study confirmed the finding of Teng and colleagues showing that VGLL4 interacts with and further showed that VGLL4 protects IRF2BP2 from ubiquitination, decreasing K48‐linked polyubiquitination. Consequently, VGLL4 protects IRF2BP2 from the proteasome‐dependent degradation pathway and stabilizes the protein . As another posttranslational regulation, IRF2BP2 can be strongly phosphorylated.…”
Section: Regulation Of Irf2bp2 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study confirmed the finding of Teng and colleagues showing that VGLL4 interacts with and further showed that VGLL4 protects IRF2BP2 from ubiquitination, decreasing K48‐linked polyubiquitination. Consequently, VGLL4 protects IRF2BP2 from the proteasome‐dependent degradation pathway and stabilizes the protein . As another posttranslational regulation, IRF2BP2 can be strongly phosphorylated.…”
Section: Regulation Of Irf2bp2 Expressionmentioning
confidence: 99%
“…Thus, the authors suggested that IFN‐γ stimulation triggers the release of IRF‐2 from the PD‐L1 promoter and regulates the dynamic association between IRF‐2 and IRF2BP2, favoring PD‐L1 expression. Whether this interaction is regulated by posttranslational modification needs to be clarified …”
Section: Biological Function Of Irf2bp2 In the Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicates that VGLL4 binds to IRF2BP2 to promote PD‐L1 expression and induces immune evasion through IRF2 inhibition in lung cancer . The binding of VGLL4 to IRF2BP2 also activates the expression of VEGF‐A in muscle cells .…”
Section: Introductionmentioning
confidence: 96%
“…21,22 A previous study indicates that VGLL4 binds to IRF2BP2 to promote PD-L1 expression and induces immune evasion through IRF2 inhibition in lung cancer. 23 The binding of VGLL4 to IRF2BP2 also activates the expression of VEGF-A in muscle cells. 24 This evidence implies that IRF2BP2 may cross talk with Hippo pathway and CTGF via binding to VGLL4.…”
Section: Introductionmentioning
confidence: 99%